Nations with high smoking rate have low SARS-CoV-2 infection and low COVID-19 mortality rate - Landoni, Giovanni; Zangrillo, Alberto; Romero García, Carolina Soledad; Faustini, Carolina; Di Piazza, Martina; Conte, Francesca; Gattarello, Simone; Kuzovlev , Artem; Likhvantsev , Valery; Puglisi, Riccardo (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the workThe effect of tobacco smoking on COVID-19 disease is debated with common sense and experts suggesting a deleterious effect and manuscripts worldwide reporting a low prevalence of active tobacco smokers among intensive care unit patients.MethodsWe categorized countries worldwide into three groups with 45% of active male smokers with data expressed as median and interquartile range [IQR] and extracted data on SARS-CoV-2 infections and COVID-19 deaths per million inhabitants. We also applied multivariate regression techniques to adjust for several epidemiological factors.ResultsCOVID-19 mortality was 13 (5-24) per million inhabitants in countries with male smokers >45% and 33 (4-133) in countries where male smokers were